Assessing the Relevance of Change Management Strategy in Moroccan Public Sector Reform - Barodi, Mohamed; Yassine Hachimi; Hicham El Ghali; Abdellatif Ryahi; Khalid Rguibi; Siham Lalaoui (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
This study examines the challenges and strategies in implementing change within Moroccan public institutions, with a particular focus on civil servants’ roles in reform success. Data were collected from 172 participants across key ministries involved in the Administrative Reform Plan (2018–2021). The research evaluates strategies for addressing resistance, fostering engagement, and managing transitions effectively, providing a nuanced understanding of how organizational changes are received and managed. To enhance the depth of analysis, this paper incorporates a comparative perspective, examining change management approaches in public reforms conducted in France and Canada. This comparison offers valuable insights into best practices and innovative solutions for managing reforms in diverse administrative and cultural contexts. The findings reveal the critical importance of adopting comprehensive and inclusive strategies that address structural and human challenges, ensuring that reforms are both effective and sustainable. By integrating empirical data with international benchmarks, this study contributes significantly to the discourse on public sector transformation and offers practical recommendations for policymakers navigating the complexities of change.